PENGEMBANGAN LKPD INTERAKTIF BERBASIS AUGMENTED REALITY BERMUATAN BUDAYA NUSANTARA PADA MATERI PECAHAN - Rohim, Dhina Cahya; Hana, Fida MAisa; Manggalastawa, Manggalastawa; Himayati, Ade Ima Afifa (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2025)
Students' difficulties in learning mathematics in elementary school are caused by its abstract nature and the use of models and teaching materials that are less interesting. Therefore, innovation is needed by providing technology-based teaching materials and linking the material to real problems such as worksheet.. This study aims to develop an interactive AR-based worksheet containing Indonesian culture that is valid and practical as an alternative teaching material and can help the learning process become more interesting. This research method is a Borg & Gall model development research with procedures including potential and problems, data collection, design planning, assessment, revision, usability testing, and final revision. Data collection techniques used observation, interviews and questionnaires. The product validity data analysis technique was carried out by calculating the percentage of the value. The validation results from material experts were 88.5%, media experts 84.5%, and cultural experts 86.8%. Therefore, the overall validation results can be categorized as very valid. The practicality test was conducted by administering a student response questionnaire, with a result of 81.9%, thus categorizing it as very practical. Therefore, it can be concluded that the development of AR-based interactive student worksheets (LKPD) with Indonesian cultural content on fractions is valid and practical for use.